Determination of Deposit Insurance Premium (LPS): Mertonâ€™s Option Theory with Co-Insurance Consideration - Pandiangan, Naomi (Operations Research: International Conference Series, 2020)
Indonesia is a developing country that implements a deposit insurance system. Deposit Insurance Agency or LPS is an Indonesian deposit insurance established in 2004, which is Indonesian still unfamiliar with LPS, both among researchers, and the general public. Almost all deposit insurance in every country including Indonesia has the same problem, the problem is how to calculate premiums and how to avoid moral hazard by banks, therefore in this study will discuss how to determine premiums from the development of Black-Scholes option theory (1973) conducted by Merton (1977). To prevent banks from engaging in moral hazard, co-insurance is considered in this study, which is banks take the risk to anticipate 'excessive risk-taking' behavior. that occurs if the value of the asset isÂ smaller than value of the deposit after joining the insurance program. So it is expected to encourage banks to beware.